Правила митної оцінки за правом світової організації торговлі - Скринька, Д. В.; Скрынька, Д. В.; Skrynka, D. (My University, 2011)
The article deals with the main provisions of WTO law on the estab- lishment of the customs value of products. The article deals, among other things, with the correlation between WTO law rules on this issue and the transfer pricing. The article points out that the customs valuation rules are complicated and that it is important to comply strictly with WTO law rules in order to take advantage of the beneﬁ ts of membership in this international organization.
Скринька Д. В. Правила митної оцінки за правом світової організації торговлі / Д. В.СКринька // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С.129-135.
Keywords: Митне право; Правила митної оцінки; Світова організація торговлі; Митна оцінка; Таможенное право; Правила таможенной оценки; Мировая организация торговли; Таможенная оценка; customs value; World Trade Organization; Customs valuation rules; customs law